2017
DOI: 10.1080/15267431.2017.1363757
|View full text |Cite
|
Sign up to set email alerts
|

When Work and Family Merge: Understanding Intragroup Conflict Experiences in Family Farm Businesses

Abstract: Family farms experience conflict in the everyday operation of the farm (Weigel & Weigel, 1990). However, family farm members rarely bring up conflicts to the other party; rather, they keep their frustration to themselves or wait until things boil over. Waters (2013) noted family farm members avoid bringing up any conflict or issues, with one son noting "basically, dad says we're doing this and I say okay" (Waters, 2013, p. 30). It is in this communicative environment that a business functions, attempting to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 82 publications
(302 reference statements)
0
21
0
Order By: Relevance
“…Hoelscher (2014) and Paskewitz and Beck (2017) did not find evidence of the effects of relationship conflict on firm performance. Other studies confirmed the adverse effects of relationship conflict on performance (Eddleston & Kellermanns, 2007; Nosé et al, 2017), firm satisfaction (Nosé et al, 2017), and growth of employment and revenue (Ensley et al, 2007).…”
Section: Findings On Intrafamily Conflict In Family Firms: the Input–mentioning
confidence: 83%
See 2 more Smart Citations
“…Hoelscher (2014) and Paskewitz and Beck (2017) did not find evidence of the effects of relationship conflict on firm performance. Other studies confirmed the adverse effects of relationship conflict on performance (Eddleston & Kellermanns, 2007; Nosé et al, 2017), firm satisfaction (Nosé et al, 2017), and growth of employment and revenue (Ensley et al, 2007).…”
Section: Findings On Intrafamily Conflict In Family Firms: the Input–mentioning
confidence: 83%
“…The family communication literature distinguishes two patterns (Sillars et al, 2014): a conformity orientation (emphasis on the homogeneity of attitudes, values, and beliefs) and a conversation orientation (open communication between family members). While higher conversation orientation seems to reduce all types of conflict, high conformity orientation may reduce cognitive conflict (Sciascia, Clinton et al, 2013) but ignite relationship conflict (Paskewitz & Beck, 2017).…”
Section: Findings On Intrafamily Conflict In Family Firms: the Input–mentioning
confidence: 99%
See 1 more Smart Citation
“…Industry support may serve as a critical resource to help offset farming demands. With respect to relationships at work, the line between work and personal lives is often blurred in farming; farmers often work where they live, work closely with family members, and farm-family conflicts are inherent in daily operations [32]. These realities may serve to increase cynicism scores in some farmers.…”
Section: Cynicismmentioning
confidence: 99%
“…Resources correlated with depersonalization/cynicism are reported to include community bond, team cohesion, and skill utilization [28]. Hence, team building, creation of a climate that values all team members' input [32], and division of labour based on individuals' skills and strengths may be helpful.…”
Section: Cynicismmentioning
confidence: 99%